الاشتراك اللغوي في كلمة ما وأثره في تنوّع الدِلالة التفسيرية جزء عمّ نموذجا - غربي ،مروه (University of Eloued جامعة الوادي, 2024)
"هذا البحث بعنوان الاشتراك اللغوي في كلمة (ما) وأثره في تنوع الدلالة التفسيرية -جزء عمّ نموذجا-، يطرح إشكالية رئيسية تمثلت في: ما أثر الاشتراك اللغوي في كلمة (ما) في تنوع الدلالة التفسيرية من خلال جزء عمّ؟ ولمعالجة هذا الإشكال اعتمدت خطة بحثية تضمنت: مقدمة ومبحثين، فالمبحث الأول عنيت من خلاله التعريف بالاشتراك اللغوي وأسبابه وأنواعه، ومعاني ما في القرآن الكريم، والمبحث الثاني تضمن الدراسة التطبيقية، اشتمل أربعة مطالب مقسّمة حسب الألفاظ المشتركة في كلمة (ما) الواردة في جزء عمّ. وفي الأخير انتهى البحث بخاتمة تضمنت ما توصلت إليه من نتائج : - نتيجة إحصائية ؛ أحصيت ثلاثين موضعا للاشتراك اللغوي في كلمة ( ما ) في جزء عم. - نتيجة متعلقة بالمعاني ؛ للاشتراك اللغوي في كلمة ( ما ) أثر كبير في الدلالة التفسيرية للآيات القرآنية وقد بينت ذلك عمليا في ثنايا البحث. This research, entitled Linguistic ambiguity in the word (ma) and its effect on the diversity of interpretive meaning - Part Amma as a model, raises a main problem represented in what is the effect of linguistic ambiguity in the word (ma) on the diversity of interpretive meaning. Interpretative significance through the part of Amma? The treatment of this problem relied on a research plan that included: an introduction and two chapters. The first chapter was concerned with defining linguistic ambiguity, its causes, types, and meanings in the Holy Qur’an. The second chapter included the applied study, and included four demands divided according to the words. Common in the word (ma) mentioned in the part of Amma. Finally, the research ended with a conclusion that included the most important results I reached: A statistical result, I counted thirty places of linguistic ambiguity in the word (ma) in the Amma section. A result related to meanings: The linguistic ambiguity in the word (ma) has a great impact on the interpretive meaning. For the verses of the Qur’an, and I have demonstrated this practically in the folds of the research.
ماستر تخصص ماستر لغة عربية ودراسات قرآنية
Keywords: الاشتراك اللغوي تنوّع الدِلالة التفسيرية القرآن الكريم معاني ما Linguistic ambiguity diversity of interpretive meaning the Holy Quran meanings of what